Transcription factor SmSPL7 promotes anthocyanin accumulation and negatively regulates phenolic acid biosynthesis in Salvia miltiorrhiza - Chen, Rui (Plant science : an international journal of experimental plant biology, 2021)
Copyright © 2021 Elsevier B.V. All rights reserved.